The global warming desk reference - Johansen, Bruce E. (Bruce Elliott), 1950- (Greenwood Press, 2002)
With global temperatures rising rapidly during the past quarter century, ʺinfrared forcing, ʺ popularly known as the ʺgreenhouse effect, ʺ has attracted worldwide concern. This book is a concise, college-level compendium of the research on global warming. It surveys the scientific consensus on the issue, describes recent findings and also considers the arguments of skeptics who doubt that global warming is a threat. Suggesting that the effects of global warming can be seen in the melting of glaciers and the dying of coral reefs, the work summarizes the potential impact on human health and on plants and animals worldwide. Concluding with possible solutions, the book contains one of the most comprehensive bibliographies on the subject.